2006
DOI: 10.1037/1091-7527.24.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of self, perceived stress, and symptom severity among patients with fibromyalgia syndrome.

Abstract: This article presents an empirical examination of the usefulness of Bowen family systems theory as a framework for understanding fibromyalgia syndrome. This cross-sectional Internet-based survey included 201 participants diagnosed with fibromyalgia syndrome. Results indicated that more severe symptoms of fibromyalgia syndrome are significantly correlated with higher levels of perceived stress, lower levels of differentiation of self, and higher levels of emotional cutoff. In addition, indicators of differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 23 publications
3
26
0
4
Order By: Relevance
“…Greater differentiation of self is thought to lead to greater interpersonal competence, emotional maturity, and lower psychological distress because it enables one to better modulate the emotional arousal experienced during challenging interpersonal situations. In contrast, less differentiated individuals are less comfortable with intimacy and/or autonomy, thought to be less effective in relationships, experience more interpersonal problems, have greater difficulty regulating emotion (Bowen 1978;Kerr and Bowen 1988), and report greater psychological distress (e.g., Bartle-Haring and Probst 2004;Kim-Appel et al 2007;Murray, et al 2006;Skowron and Friedlander 1998;Skowron et al 2004). In emotionally charged interpersonal situations, less differentiated persons are thought to become more emotionally reactive and engage in emotional cutoff or fusion with others in response to stress (Nichols and Schwartz 2004).…”
Section: Introductionmentioning
confidence: 91%
“…Greater differentiation of self is thought to lead to greater interpersonal competence, emotional maturity, and lower psychological distress because it enables one to better modulate the emotional arousal experienced during challenging interpersonal situations. In contrast, less differentiated individuals are less comfortable with intimacy and/or autonomy, thought to be less effective in relationships, experience more interpersonal problems, have greater difficulty regulating emotion (Bowen 1978;Kerr and Bowen 1988), and report greater psychological distress (e.g., Bartle-Haring and Probst 2004;Kim-Appel et al 2007;Murray, et al 2006;Skowron and Friedlander 1998;Skowron et al 2004). In emotionally charged interpersonal situations, less differentiated persons are thought to become more emotionally reactive and engage in emotional cutoff or fusion with others in response to stress (Nichols and Schwartz 2004).…”
Section: Introductionmentioning
confidence: 91%
“…Chronic pain from arthritis, for example, may itself be a stressor; in this overtaxed state, individuals may narrow their focus to negative experiences rather than the more demanding processing of both positive and negative information which has been linked with well-being (Davis, Zautra, & Smith, 2004). For example, among individuals with rheumatoid arthritis and fibromyalgia, more severe and/or chronic symptoms were related to elevated levels of stress (Murray, Daniels, & Murray, 2006; Tak, Hong, & Kenneday, 2007). …”
Section: Chronic and Somatic Health Problemsmentioning
confidence: 99%
“…Furthermore, Bowen (1978) and Kerr and Bowen (1988) posited that individuals lower in differentiation of self will become more stressed and remain stressed for more extended amounts of time compared to individuals with higher levels of differentiation of self. Murdock and Gore (2004) and Murray, Daniels, and Murray (2006) found support for Bowen's predictions in that they discovered that differentiation of self works as a moderator between differentiation of self and stress symptoms. Murdock and Gore (2004) also found that coping styles and differentiation were related to differentiation of self in that higher levels of differentiation were related to the greater use of reflective coping strategies and reactive and suppressive techniques of dealing with stress were related to lower levels of differentiation.…”
Section: The Relationship Between Trauma and Differentiation Of Selfmentioning
confidence: 58%